Post-operative complications of ilizarov technique in tibial non-union- A prospective study (Journal of Dhaka National Medical College & Hospital, 2024)
Background: Non-union of the tibia is a significant problem for patient and surgeon, and in many situations the patient has undergone more than one surgical procedure, and lost considerable time from his job and his life. Ilizarov technique is an effective method for treatment of tibial non-union. It has low rate of complication. Objective: To assess the post-operative complications of Ilizarov technique in tibial non-union.Methodology: This prospective study was carried out at the Department of Orthopedic Surgery at Chittagong Medical College Hospital, Chittagong from June 25, 2018 to June 24, 2019. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science.Result: out of 12 cases, 8 (66.7%) were in